1993
DOI: 10.1111/j.1432-1033.1993.tb17650.x
|View full text |Cite
|
Sign up to set email alerts
|

Fructose‐1,6‐bisphosphatase of the yeast Kluyveromyces lactis

Abstract: The fructose-l,6-bisphosphatase [Fru(l ,6)P2ase] gene of the budding yeast, Kluyveromyces luctis, was cloned and sequenced. The gene encodes one open reading frame predicting a 354-amino-acid polypeptide. The polypeptide is different from other Fru(l,6)P2ases in that it contains a short amino-acid-insert region close to a basic residue located at the binding site for the allosteric inhibitor AMP. Comparison of the biochemical properties of the K. Zuctis enzyme with its closest homolog, the Succhuromyces cerevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
3
6
1
Order By: Relevance
“…In particular, the amount of the KlSDH1 mRNA from ethanol and glycerol cultures was very similar to that of cells grown in 1 and 7% glucose, indicating that the gene was not sensitive to carbon catabolite repression. These results are in agreement with the general observation that respiratory genes of K. lactis escape transcriptional repression during growth on glucose (26,35,36,53). No KlSDH1 mRNA could be detected in the Klsdh1⌬ strain grown on different concentrations of glucose or lactate (lanes 8, 9, and 10).…”
Section: Resultssupporting
confidence: 91%
“…In particular, the amount of the KlSDH1 mRNA from ethanol and glycerol cultures was very similar to that of cells grown in 1 and 7% glucose, indicating that the gene was not sensitive to carbon catabolite repression. These results are in agreement with the general observation that respiratory genes of K. lactis escape transcriptional repression during growth on glucose (26,35,36,53). No KlSDH1 mRNA could be detected in the Klsdh1⌬ strain grown on different concentrations of glucose or lactate (lanes 8, 9, and 10).…”
Section: Resultssupporting
confidence: 91%
“…5) revealed that the level of KlFBP1-speci®c mRNA in glucosegrown wild-type cells is reduced compared to that in glycerol-and ethanol-grown cells. The repression observed in strain JA6 is stronger than that described previously for strain 2UV21 (Zaror et al 1993). Similarly, the amount of KlPCK1 mRNA expressed in glucose medium is lower than that in ethanol.…”
Section: Resultscontrasting
confidence: 68%
“…The protein from K. lactis contains a short amino acid insert sequence near the binding site of the allosteric inhibitor AMP absent in the S. cerevisiae protein. This amino acid stretch seems to be responsible for the lower sensitivity to AMP inhibition of this enzyme with respect to that of S. cerevisiae [237]. The expression of the gene is usually repressed in the presence of glucose, although differences in the degree of repression are observed among species.…”
Section: Gluconeogenesismentioning
confidence: 93%
“…This reaction is the terminal step of gluconeogenesis and therefore the corresponding enzyme is required for metabolism of every non‐sugar carbon source. The gene encoding this enzyme has been isolated from S. pombe [236] and from K. lactis [237] and the enzyme has also been purified from C. utilis [238]. The protein from K. lactis contains a short amino acid insert sequence near the binding site of the allosteric inhibitor AMP absent in the S. cerevisiae protein.…”
Section: Gluconeogenesismentioning
confidence: 99%